Quantitative MRI analysis in children with multiple sclerosis: a multicenter feasibility pilot study - Chitnis, Tanuja; Guttmann, Charles R; Zaitsev, Alexander; Musallam, Alexander; Weinstock-Guttman, Bianca; Yeh, Ann; Rodriguez, Moses; Ness, Jayne; Gorman, Mark P; Healy, Brian C; Kuntz, Nancy; Chabas, Dorothee; et al. (BMC neurology, 2013)
Background Pediatric multiple sclerosis (MS) is a rare disorder with significant consequences. Quantitative MRI measurements may provide significant insights, however multicenter collaborative studies are needed given the small numbers of subjects. The goal of this study is to demonstrate feasibility and evaluate lesion volume (LV) characteristics in a multicenter cohort of children with MS. Methods A common MRI-scanning guideline was implemented at six member sites of the U.S. Network of Pediatric MS Centers of Excellence. We included in this study the first ten scans performed at each site on patients meeting the following inclusion criteria: pediatric RRMS within 3 years of disease onset, examination within 1 month of MRI and no steroids 1 month prior to MRI. We quantified T2 number, T2-LV and individual lesion size in a total of 53 MRIs passing quality control procedures and assessed gadolinium-enhancing lesion number and LV in 55 scans. We studied MRI measures according to demographic features including age, race, ethnicity and disability scores, controlling for disease duration and treatment duration using negative binomial regression and linear regression. Results The mean number of T2 lesions was 24.30 ± 19.68 (range:1–113) and mean gadolinium-enhancing lesion count was 1.85 ± 5.84, (range:0–32). Individual lesion size ranged from 14.31 to 55750.60 mm 3 . Non-white subjects had higher T2–LV (unadjusted p T2-LV = 0.028; adjusted p T2-LV = 0.044), and maximal individual T2-LV (unadjusted p Max = 0.007; adjusted p Max = 0.011) than white patients. We also found a trend toward larger mean lesion size in males than females (p = 0.07). Conclusion Assessment of MRI lesion LV characteristics is feasible in a multicenter cohort of children with MS.